KEPEMIMPINAN DEMOKRATIS DALAM UPAYA MENINGKATKAN MOTIVASI KERJA PEGAWAI - Syamsidar, Syamsidar; Yustikarini, Listiya (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research is motivated by hoping all people for a fair, wise and democratic leader. The purpose of this study to find out whether the adoption of a democratic leadership style that can increase the work motivation of South OKU Regency Education of employees. This study uses a qualitative approach, with data collection techniques namely interviews, observation, and documentation. Data was obtained from the Head of Middle School Development, Head of Sub-Division of Staffing, Staff of the Education Office, and two headmasters of South OKU District. The results of the study at the South OKU Regency Education Office are visible in the atmosphere of family and happiness in the workplace. Rarely employees who leave work hours for a long time, even though the leader is not in the office.The employees work energetically and without pressure. One of the triggers for increasing the motivation of employee working in the South OKU Regency Education Office is the leadership style is very democratic. Where, in this case the head of the South OKU Regency Education Agency treats all employees as families not as superiors and subordinates. Tolerance and high respect for all employees make them feel valuable, and trigger for employees to improve the quality of their work.